Dielectric investigation of high-k yttrium copper titanate thin films. Issue 5 (11th January 2016) - Monteduro, Anna Grazia; Ameer, Zoobia; Martino, Maurizio; Caricato, Anna Paola; Tasco, Vittorianna; Lekshmi, I. C.; Rinaldi, Ross; Hazarika, Abhijit; Choudhury, Debraj; Sarma, D. D.; Maruccio, Giuseppe
Abstract : We report on the first dielectric investigation of high- k yttrium copper titanate thin films, which were demonstrated to be very promising for nanoelectronics applications. Abstract : We report on the first dielectric investigation of high- k yttrium copper titanate thin films, which were demonstrated to be very promising for nanoelectronics applications. The dielectric constant of these films is found to vary from 100 down to 24 (at 100 kHz) as a function of deposition conditions, namely oxygen pressure and film thickness. The physical origin of such variation was investigated in the framework of universal dielectric response and Cole–Cole relations and by means of voltage dependence studies of the dielectric constant. Surface-related effects and charge hopping polarization processes, strictly dependent on the film microstructure, are suggested to be mainly responsible for the observed dielectric response. In particular, the bulky behaviour of thick films deposited at lower oxygen pressure evolves towards a more complex and electrically heterogeneous structure when either the thickness decreases down to 50 nm or the films are grown under high oxygen pressure.